Respostas fisiológicas de goiabeira "Paluma" parasitada por Meloidogyne mayaguensis sob condições controladas e de campo - Bispo, Wilka Messner da Silva (2010)
The fruticulture in the Espírito Santo State is anactivity of great social and economical expression, accountingfor much of the agricultural income of the state. Given the importance of this economy segment, it is necessary to search for a biggerdiversification of the crops, in order to keep the consumer market active. Accordingly, the guava culture has shown to be a very effective alternativein diversification, because it has a great production and sale potential, which makes relevant the knowledge of their positive features and their limitations, with the purpose of expanding the market.There are,however, many phytosanitary problems in the regions of production, and these problems are capable to affect the development and the productivity of the cultivated areas. The cropsensitivity to root-knot nematodes is highlighted.So, this work aimed to evaluate the nematodeeffectof Meloidogyne mayaguensis (Sin.:M. enterolobii)on the plantsby analyzing the kinetics of the transient chlorophyll a fluorescence emission, photosynthetic pigments contents and growth, correlating morphological andphysiologicalchangesin the plants, bothunder field and greenhouse conditions. In the field, the infested plants showed lower photochemical efficiency in comparison to healthy plants, in both periods. The levels of leafpigments showed a similar trend to that found in photochemical responses. The healthy plants had higher values of chlorophyll a and b and carotenoids, about 1.5 times higher than the value found for the symptomatic ones. Deficiencies in the photochemical performance of the parasitized plants also reflected in the lowproductivity and in the formation of smaller fruits. The healthy plants were about 2 times more productive than the asymptomatic and 6.5 times more productive than the symptomatic plants. It was also noted that, in thegreenhouse,atthe beginning of thevegetative growth, there were no visual changes in the shoots of plants infested either for growth and SPADreadings. This behavior demonstrates one of the major problems faced by nurseries, which is the non-observation of the root-knot nematode symptoms in short-term, which encourage the tradeof infected plantsand the nematode dissemination